Peculiarities of the development of oral speech for foreign students - Zlotnyk-Shagina, Olga (Current issues of Ukrainian linguistics: theory and practice, 2021)
The article considers oral speech as the main tool in the process of learning the Ukrainian language for foreign students. Therefore, oral speech should always be developed and improved. And for foreign students, the development of oral speech in the study of the Ukrainian language is the most important aspect. Without oral coherent speech it is impossible to fully master the Ukrainian language. There are many different methods of speech development for foreign students, for example, Ukrainian literature is closely related to the language and culture of the Ukrainian people, which is ideal for the development of oral speech of foreign students. to determine the role of oral speech in language learning and the formation of students' professional understanding of the essence of communicative activity, nature, components and forms of communication, features of verbal and nonverbal communication code, the influence of national and cultural factors on communication in both professional and everyday activities. As oral presentations become an increasingly important feature of higher education, it is important to find out what oral communication skills students need to function successfully in an academic context. Thus, this specific presentation aims to identify and describe students' assessment of their own skills in the oral academic Ukrainian language, in particular, to compare how good and important their skills are. Oral speech allows students to form a holistic view of the nature and functions of communication in society, the technical means of communication; to acquaint foreign students with the basic laws of communication, with the verbal and nonverbal code of communication, types of communication barriers; to expand the active and passive vocabulary in the field of professional speech of foreign students of philology; to form basic practical skills necessary for communication in the field of intercultural communication; to raise the general educational and cultural level of foreign students. The article presents options for the development of oral speech and presents examples of exercises that contribute to the rapid study of the Ukrainian language as a foreign language and the development of oral speech.
Keywords: oral speech, learning Ukrainian as a foreign language, listening, speaking, dialogue, monologue, written language, reading, writing.